Digital Transformation in Business Licensing Innovation Through a One-Stop Service Management Policy - Halimatus Zahra (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2025)
This study aims to: first, explore the digital transformation undertaken by the Jember Regency government in conducting business licensing through a one-stop service policy; second, analyze the impact of digital transformation on business licensing innovation through a one-stop service management policy; and third, explore the effectiveness of business licensing innovation through a one-stop service management policy. Based on these objectives, this study is expected to contribute: first, contributing to institutions to always innovate in services by implementing digital transformation for effectiveness in public services; and second, contributing to the community that digital transformation can make services more effective in terms of time and cost, especially if carried out through a one-stop service. Thus, there is no long bureaucracy. The objectives and contributions can be achieved through a qualitative research approach with a case study type. Researchers directly explore the one-stop service management policy implemented in Jember Regency since 2021. Researchers conducted observations, interviews, and traced data through a documentation process. Analysis used the Miles and Huberman model, and data validity tests used source and technique triangulation. The results of this study, first, the Jember Regency government in business licensing services innovated by changing the system to a one-stop and digital-based system, so that business actors did not have long bureaucratic licensing processes. Second, the impact of one-stop shop management, coupled with digital transformation, is fast, easy, and affordable service. Third, business licensing innovations are effective in preventing fraud and extortion, as well as being time-efficient.